2005
DOI: 10.1103/physrevb.71.184117
|View full text |Cite
|
Sign up to set email alerts
|

Origin of warping in theEeJahn-Teller problem: Quadratic vibronic coupling versus anharmonicity and application toNaCl:Rh2+

Abstract: A general method is suggested which allows one to separate the quadratic, cubic, and pseudo Jahn-Teller contributions to the warping of the adiabatic potential energy surface ͑APES͒ of the E e problem employing ab initio calculations. Numerical results were obtained for NaCl: Rh 2+ in a cluster approximation and triangular molecules ͑Na 3 ,K 3 ,Cu 3 ,Ag 3 ͒ using density functional theory ͑DFT͒ and multireference second-order perturbation theory ͑CASPT2͒ methods. A largely unexpected result is that the contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 52 publications
4
78
1
Order By: Relevance
“…In a previous work 11 analyzing the different factors contributing to the barrier, B, we showed that when the E g term of an octahedral d 9 complex splits because of distortion in the Q θ coordinate, the energy surfaces of the resulting A 1g and B 1g electronic states can be written as …”
Section: Analysis Of the Calculated Q θ Dependencementioning
confidence: 99%
See 4 more Smart Citations
“…In a previous work 11 analyzing the different factors contributing to the barrier, B, we showed that when the E g term of an octahedral d 9 complex splits because of distortion in the Q θ coordinate, the energy surfaces of the resulting A 1g and B 1g electronic states can be written as …”
Section: Analysis Of the Calculated Q θ Dependencementioning
confidence: 99%
“…This mechanism of energy lowering is sometimes termed the pseudo-JT effect. 11,12 If we only consider the excited states arising from the e g 2 4s 1 configuration for NaCl:Ni + , the difference between V PJT (A 1g ) and V PJT (B 1g ) can be understood by looking at Figure 3, taking into account that the 4s orbital can only be coupled to the 3z 2 − r 2 one through the W 1θ (r) operator. As in the B 1g state there are two electrons in the a 1g *(∼3z 2 −r 2 ) orbital and only one in the A 1g state ( Figure 3) the energy gain due to this mechanism for B 1g is essentially twice that for A 1g .…”
Section: Analysis Of the Calculated Q θ Dependencementioning
confidence: 99%
See 3 more Smart Citations